Market Power of the Input Supplier, Technology Transfer and Consumer Welfare - Jiyun Cao; Arijit Mukherjee (Center for Economic Studies and ifo Institute (CESifo), 2014)
It is believed that market power of the input supplier, charging a linear price, is detrimental for the consumers since it creates the double marginalisation problem. We show that this view may not be true if the final goods producers can adopt strategies to reduce rent extraction by the input supplier. Market power of the input supplier may encourage a final goods producer either to license its technology to a competitor or to adopt a less distortionary technology licensing contract. Both these effects may create higher consumer welfare under market power of the input supplier compared to a competitive input market.
Keywords: J51; L12; L13; L24; 330; consumer surplus; labour union; technology licensing